NILAI DIAGNOSTIK SKOR STROKE DAVE UNHAS PADA PENDERITA STROKE ISKEMIK KARDIOEMBOLI DENGAN FIBRILASI ATRIUM - Supardin,* David Gunawan,* Cahyono Kaelan* (Neurona Majalah Kedokteran Neuro Sains, 2019)
INTRODUCTION IT IS IMPORTANT TO DIAGNOSE CARDIOEMBOLIC ISCHEMIC STROKE QUICKLY ESPECIALLY IN THE ABSENCE OF CTSCANMRI BESIDES HAVING A POOR PROGNOSIS CARDIOEMBOLIC ISCHEMIC STROKE ALSO HAS HIGH DISABILITY AND DEATH RATES